2020
DOI: 10.1101/2020.10.24.353581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trade-Offs Between Antibacterial Resistance and Fitness Cost in the Production of Metallo-β-Lactamase by Enteric Bacteria Manifest as Sporadic Emergence of Carbapenem Resistance in a Clinical Setting

Abstract: Meropenem is a clinically important antibacterial reserved for treatment of multi-resistant infections. In meropenem-resistant bacteria of the family Enterobacteriales, NDM-1 is considerably more common than IMP-1, despite both metallo-β-lactamases (MBLs) hydrolysing meropenem with almost identical kinetics. We show that blaNDM-1 consistently confers meropenem resistance in wild-type Enterobacteriales, but blaIMP-1 does not. The reason is higher blaNDM-1 expression because of its stronger promoter. However, th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…By contrast, a greater number of ESBL resistance genes were detected post incubation than direct from water filter. There has been an increase in data surrounding the relative fitness costs on bacteria that harbour resistance markers in the absence of selection pressure, notably those associated with large mobile plasmids (Cheung et al, 2021). We hypothesise that the loss here is due to carbapenemases being less stable within bacteria than ESBLs, similar to outcomes observed by Cheung et al (2021).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…By contrast, a greater number of ESBL resistance genes were detected post incubation than direct from water filter. There has been an increase in data surrounding the relative fitness costs on bacteria that harbour resistance markers in the absence of selection pressure, notably those associated with large mobile plasmids (Cheung et al, 2021). We hypothesise that the loss here is due to carbapenemases being less stable within bacteria than ESBLs, similar to outcomes observed by Cheung et al (2021).…”
Section: Discussionmentioning
confidence: 57%
“…There has been an increase in data surrounding the relative fitness costs on bacteria that harbour resistance markers in the absence of selection pressure, notably those associated with large mobile plasmids (Cheung et al, 2021). We hypothesise that the loss here is due to carbapenemases being less stable within bacteria than ESBLs, similar to outcomes observed by Cheung et al (2021). However, more extensive research is needed to both further our understanding of AMR as well as guide laboratory practice.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, studies in E. coli showed that the overall assembly rates for virulence factors like FimD and UshC are dependent on how well features in these protein sequences can be handled by the components of the host cell's biosynthetic machinery (74). Similarly, for b-lactamases, a substantial fitness cost of carbapenem resistance has been quantified and linked to amino acid starvation due to codon usage incompatibility and other issues associated with maintaining sufficiently high expression levels of the carbapenemase (75).…”
Section: Discussionmentioning
confidence: 99%